Effect of water to cement ratio to the mechanical properties of oil palm shell lightweight concrete - Nor Faezah, Affri (2015)
Oil palm shell (OPS) is a waste material that is obtained by crushing the palm nut in the palm oil mills during the extraction of palm oil. Replacing coarse aggregate with OPS in concrete is one of the way to optimize the use of natural waste material. In this research, crushed OPS was used to replace the coarse aggregate in the production of lightweight aggregate concrete (LWAC). Various water to cement ratio was also used in this research to investigate the effect of water to cement ratio to the mechanical properties of OPS lightweight concrete. The compressive strength, splitting tensile strength, flexural strength and static modulus elasticity test were conducted. The effect of the research was studied at 7 days and 28 days. The test result showed that higher water to cement ratio gives lowest strength to the concrete. Through the results, OPS have been found useful in replaced the coarse aggregate in concrete. However, the water to cement ratio greatly affect the behaviour of OPS lightweight aggregate concrete.